PERBANDINGAN KETERAMPILAN BERFIKIR KRITIS SISWA MENGGUNAKAN MODEL PEMBELAJARAN PBL DENGAN PjBL PADA MATA PELAJARAN PAI-BP DI SMP NEGERI 5 BUKITTINGGI - Lucky Ramadhan; Arifmiboy; Wedra Aprison; Yelfi Dewi S (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research was motivated by the low level of students' critical thinking skills in Islamic Religious Education learning. This condition is indicated by the percentage of students' critical thinking abilities, where 50% of students are categorized as having moderate critical thinking skills, 30% as having critical thinking skills, and 20% as not demonstrating critical thinking skills. To overcome this problem, effective learning models are needed to improve students' critical thinking abilities. Two learning models considered relevant are Problem Based Learning (PBL) and Project Based Learning (PjBL). However, both models have their own advantages and limitations, therefore it is necessary to examine the effectiveness of these two learning models in the learning process. This study used a quantitative approach with a 2×2 factorial design. The population consisted of 145 students, while the sample involved 58 students selected through random sampling and divided into two learning groups. Data on students' critical thinking skills were collected through essay tests and analyzed using a t-test, considering subgroups of students with high and low prior abilities. The results showed that students’ critical thinking skills using the Problem Based Learning model were better than those using the Project Based Learning model among students with high prior ability (p = 0.038 < 0.05). Meanwhile, for students with low prior ability, there was no significant difference between the two learning models (p = 0.91 > 0.05). Overall, there was a significant difference in students’ critical thinking skills between the PBL and PjBL models regardless of students’ prior abilities (p = 0.031 < 0.05).